"I have to be the example": Motherhood as a lens for understanding physical activity among low-income women. (8th August 2022) - MacNell, Lillian; Hardison-Moody, Annie; Wyant, Amanda; Bocarro, Jason N.; Elliott, Sinikka; Bowen, Sarah
Abstract: Parents and people living in poverty are less likely to engage in leisure-time physical activity, yet these groups are underrepresented in socio-ecological studies of activity. To understand barriers and facilitators to leisure-time physical activity within these groups, this study draws on 138 interviews with low-income U.S. mothers to highlight the ways in which motherhood framed their decisions and ability to engage in physical activity. The challenges they faced were filtered through their practices as mothers; for example, they had little time and energy to be active because of the demands of daily childrearing and household labor. In addition, their strategies around leisure-time physical activity were tied to ideas of good mothering; for example, they sought opportunities that were free or low-cost for the entire family. Understanding how motherhood shapes low-income women's leisure-time physical activity can inform interventions and policies to increase physical activity among this population.